Seasonality in malaria transmission: implications for case-management with long-acting artemisinin combination therapy in sub-Saharan Africa - Cairns,ME; Walker,PGT; Okell,LC; Griffin,JT; Garske,T; Asante,KP; Owusu-Agyei,S; Diallo,D; Dicko,A; Cisse,B; Greenwood,BM; Chandramohan,D; et al. (Malaria Journal, 2015)
Background: Long-acting artemisinin-based combination therapy (LACT) offers the potential to prevent recurrentmalaria attacks in highly exposed children. However, it is not clear where this advantage will be most important, anddeployment of these drugs is not rationalized on this basis.Methods: To understand where post-treatment prophylaxis would be most beneficial, the relationship betweenseasonality, transmission intensity and the interval between malaria episodes was explored using data from six cohortstudies in West Africa and an individual-based malaria transmission model. The total number of recurrent malariacases per 1000 child-years at risk, and the fraction of the total annual burden that this represents were estimated forsub-Saharan Africa.Results: In settings where prevalence is less than 10 %, repeat malaria episodes constitute a small fraction of thetotal burden, and few repeat episodes occur within the window of protection provided by currently available drugs.However, in higher transmission settings, and particularly in high transmission settings with highly seasonal transmission, repeat malaria becomes increasingly important, with up to 20 % of the total clinical burden in children estimatedto be due to repeat episodes within 4 weeks of a prior attack.Conclusion: At a given level of transmission intensity and annual incidence, the concentration of repeat malariaepisodes in time, and consequently the protection from LACT is highest in the most seasonal areas. As a result, thedegree of seasonality, in addition to the overall intensity of transmission, should be considered by policy makers whendeciding between ACT that differ in their duration of post-treatment prophylaxis.